Field notes and letter to Thomas H. Kent from Rene Laubach regarding a Mourning Warbler sighting, spring 1983 - Laubach, Reneet al (1983)
Spring report of birds found in central Iowa contributed by Rene Laubach. A brief letter to Thomas H. Kent from Laubach regarding a Mourning Warbler sighting is included. There is also a message indicating this will be the last contribution to the field reports from Laubach due to a move out of state. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed/flatbed